2023
DOI: 10.1038/s41397-023-00314-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study on pharmacological outcomes of musculoskeletal pain in UK Biobank

Abstract: The pharmacological management of musculoskeletal pain starts with NSAIDs, followed by weak or strong opioids until the pain is under control. However, the treatment outcome is usually unsatisfying due to inter-individual differences. To investigate the genetic component of treatment outcome differences, we performed a genome-wide association study (GWAS) in ~ 23 000 participants with musculoskeletal pain from the UK Biobank. NSAID vs. opioid users was compared as a re ection of the treatment outcome of NSAIDs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In a recent genome-wide association study (GWAS) performed on 23,000 participants with musculoskeletal pain from the UKB, the authors identified a hit in SNP (rs549224715) on chromosome 4 to be significantly associated with analgesic ladder switch from non-steroidal anti-inflammatory drugs (NSAIDs) to opioids for pain management by comparing NSAID users and opioids users. In the subsequent network and pathway analysis on functional genes located on the significant loci, EGFR was identified as a central hub [72], further suggesting its potential role in pain progression.…”
Section: Clinical Studies and Genetic Associationsmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent genome-wide association study (GWAS) performed on 23,000 participants with musculoskeletal pain from the UKB, the authors identified a hit in SNP (rs549224715) on chromosome 4 to be significantly associated with analgesic ladder switch from non-steroidal anti-inflammatory drugs (NSAIDs) to opioids for pain management by comparing NSAID users and opioids users. In the subsequent network and pathway analysis on functional genes located on the significant loci, EGFR was identified as a central hub [72], further suggesting its potential role in pain progression.…”
Section: Clinical Studies and Genetic Associationsmentioning
confidence: 98%
“…In the initial report on EGFR involvement in pain, it was shown that EREG is the only ligand among those tested (e.g., amphiregulin, EGF, TGF-α, Betacellulin) that can not only elicit an acute nociceptive response but also amplify existing pain when injected intrathecally [70]. Recently, it has been shown that other ligands like EGF [25], HB-EGF, and a peptide toxin mimicking the EGF domain of HB-EGF [69,72] can also elicit an acute nociceptive response when injected at the periphery. Downregulation of TGFαin DRGs, has been shown to suppress CCL2/CCR2 signaling and reduce pain in a surgically induced osteoarthritis pain model [73].…”
Section: Egfr Involvement In Pain In Animal Modelsmentioning
confidence: 99%